Research on the relationship between enterprise internationalization degree and performance based on the multi-index simplified model - Yang, Xue; Ismail, Md Daud (Edelweiss Applied Science and Technology, 2025)
In view of the long application time of the multi-index simplified model in current research, which results in low operational performance accuracy, this paper conducts a comprehensive study on the relationship between enterprise internationalization degree and performance based on the multi-index simplified model. First, the application system of the multi-index simplified model is constructed, the application of the model is defined, and the correlation characteristics and dimensional features of the model are analyzed. Then, based on the relationship between enterprise internationalization degree and performance, the factor set and evaluation set are defined. The relationship between internationalization degree and performance is derived through the mapping of the multi-index simplified model. The multi-index simplified information is processed, completing the application of the model. The simulation experiment results indicate that the overall operational performance of the proposed model is highly accurate, with a short operation time and strong practicality.